The Influence of COVID-19 on Entrepreneur's Psychological Well-Being - Xu, Zhengda; Jia, Heqi (Frontiers in Psychology, 2022)
This research focuses on the influence of COVID-19 on entrepreneurs' psychological well-being (PWB) in China. A start-up's performance is believed to play an important moderating role. This study uses 2 years of tracking data of 303 entrepreneurs from Shandong Providence, China. Based on conservation of resources (COR) theory, this study found that COVID-19 will significantly decrease entrepreneurs' PWB. A start-up's past performance will enhance the negative influence of COVID-19 on entrepreneurs' PWB. This study contributes to the literature on entrepreneurship, COR, and PWB. The findings can also guide entrepreneurs to maintain well-being during the pandemic and post-pandemic era.